Synthesis of Molecularly Imprinted Polymer via Emulsion Polymerization for Application in Solanesol Separation - Zhao, Guojie; Liu, Jing; Liu, Minghong; Han, Xiaobin; Peng, Yulong; Tian, Xiatian; Liu, Jialei; Zhang, Shaofeng (Applied sciences, 2020)
High-purity solanesol can be used for pharmaceutical applications, but the current method for purifying solanesol has high cost and difficult continuous operation, and the use of molecular imprinting to purify natural products is a hot research topic of current research. Solanesol molecularly imprinted polymers were synthesized via emulsion polymerization for the first time. The morphology of the SSO-MIPs was observed with a scanning electron microscope, and the effects of the synthesis time, initiator dosage, functional monomer dosage, and cross-linking agent dosage on the adsorption effects under high-temperature and rapid synthesis conditions were discussed. The results demonstrate that the optimum synthesis conditions were a ratio of the template molecules to the functional monomers to the cross-linking agents of 1:8:30 (mol:mol:mol), 10 mg of the initiator, and a synthesis temperature of 70 °C. The imprinting factor of SSO-MIPs synthesized under the optimized process was found to reach 2.51, and the SSO-MIPs synthesized by this method exhibited a good adsorption effect, emitted less pollution during the synthesis process, and are convenient for demulsification. This research reports a reliable method for the synthesis of solanesol molecularly imprinted polymers.